2021
DOI: 10.1109/access.2021.3072075
|View full text |Cite
|
Sign up to set email alerts
|

Image Encryption and Authentication With Elliptic Curve Cryptography and Multidimensional Chaotic Maps

Abstract: Many researchers have used the properties of the popular Elliptic Curve Cryptography(ECC) to devise a stronger and faster image encryption algorithm to assure the secrecy of images during online transmission. In this paper, a robust Elliptic curve based image encryption and authentication model for both grayscale and color images has been proposed. The model uses the secure Elliptic Curve Diffie-Hellman(ECDH) key exchange to compute a shared session key along with the improved ElGamal encoding scheme. 3D and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Furthermore, the results are prepared based on three different directions horizontal, vertical, and diagonal. [27,32] and comparable with the method [26]. For the Boat image, the C-RSA has performed better than Chaos, Chaos-DNA, and DNA-BST [32].…”
Section: Correlation Coefficient (Cf) Analysismentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the results are prepared based on three different directions horizontal, vertical, and diagonal. [27,32] and comparable with the method [26]. For the Boat image, the C-RSA has performed better than Chaos, Chaos-DNA, and DNA-BST [32].…”
Section: Correlation Coefficient (Cf) Analysismentioning
confidence: 82%
“…The method generates an ample keyspace of sequence and robust against various attacks, and resolves the transmission and storage of encrypted data. Parida et al [27] proposed the Elliptic Curve Diffie-Hellman key exchange technique for the shared session key. Here authors use the 3D and 4D Arnold cat maps for image data security.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, a robust elliptic curve-based image encryption and authentication model for grayscale and colour images have been presented [47]. The model uses the secure elliptic curve Diffie-Hellman key exchange to compute a shared session key with the enhanced ElGamal encoding scheme.…”
Section: Related Workmentioning
confidence: 99%
“…Our projected architecture showed that there is no need for an extensive public key database. Parida et al [47] The work presents elliptic curve-based image encryption and authentication model that uses a secure elliptic curve Diffie-Hellman key exchange to compute a shared session key with the enhanced ElGamal encoding scheme.…”
Section: Pourasad Ranjbarzadeh Andmentioning
confidence: 99%
“…[14]. It also serves to security-related scenarios such as information hiding [15], authentication [16,17], privacy [18], etc. Furthermore, cryptography is supported by a variety of enabling technologies and sciences including radix 2 n [19] and modular arithmetics [20], quantum computing [21,22], coding and information theory [23,24], Very Large Scale Integration [25], chaos theory [26], and error management techniques [27] are used to support cryptography.…”
Section: Introductionmentioning
confidence: 99%